Determination of melamine in infant formulas by fluorescence quenching based on the functionalized Au nanoclusters. (December 2016) - Yang, Xiupei; Jia, Zhihui; Tan, Zhijing; Xu, Hua; Luo, Na; Liao, Xiangjun
Abstract: An environmentally benign and cost-effective assay was developed for the fast determination of melamine (MA) with tiopronin-stabilized gold nanoclusters (TPN-AuNCs) as a fluorophore. The TPN-protected gold nanoclusters which exhibit strong fluorescence emission were prepared by a simple one-vessel procedure. Upon addition of melamine to TPN-AuNCs, a dramatic decrease in their fluorescence intensity was observed, attributing to the electrostatic attraction between the MA and the surface of the TPN-AuNCs which induces the aggregation of TPN-AuNCs. Parameters affecting the detection of MA were investigated including pH, amount of TPN-AuNCs, temperature as well as reaction time. Under the optimized experimental conditions, trace amounts of MA could be analyzed based on the reduction in the fluorescence intensity of TPN-AuNCs. A linear relationship was established at concentrations ranging from 0.09 μM to 100 μM. The detection limit at 32 nM was achieved for this method. The developed method has been successfully applied to the determination of MA in several spiked infant formulas samples purchased from a local supermarket. Excellent recoveries at 92.0–102.2% and precision (RSD: 1.14–2.80%) were attained, respectively, which confirmed the great potential of tiopronin-stabilized gold nanoclusters toward practical measurement of melamine in infant formulas of samples. Highlights: A new tiopronin-stabilized gold nanoclusters (TPN-AuNCs) is prepared. Melamine can be detected based on the as-prepared TPN-AuNCs. This work provides a simple technique to quantify melamine in infant formulas.